1999
DOI: 10.1159/000029352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bronchodilator Effects of Salbutamol Delivered via a Metered-Dose Inhaler with Spacer, a Dry-Powder Inhaler, and a Jet Nebulizer in Patients with Chronic Obstructive Pulmonary Disease

Abstract: The aim of this study was to compare the bronchodilator effects of salbutamol delivered via three different devices: a dry-powder inhaler (DPI), a metered-dose inhaler (MDI) with a large-volume spacer and a jet nebulizer (NEB) in patients with stable chronic obstructive pulmonary disease (COPD). Ten male patients with stable COPD [age: 67.2 ± 3.8 years, forced expiratory volume in 1 s (FEV1): 1.56 ± 0.32 liters] were studied in a randomized, double-blind and crossover manner. Each patient received 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
(40 reference statements)
2
13
0
Order By: Relevance
“…In contrast to other trials patients who had already received systemic steroids prior to hospital admission were not excluded. Nevertheless the degree of spirometric improvement registered in both of the treatment groups, ¡30% early improvement, is consistent with that found in other trials [9][10]. PFTs improved in both treatment groups, particularly in the first few days after onset of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast to other trials patients who had already received systemic steroids prior to hospital admission were not excluded. Nevertheless the degree of spirometric improvement registered in both of the treatment groups, ¡30% early improvement, is consistent with that found in other trials [9][10]. PFTs improved in both treatment groups, particularly in the first few days after onset of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…PFTs improved in both treatment groups, particularly in the first few days after onset of treatment. A similar evolution as seen in the trial conducted by NIEWOEHNER et al [10] and SEEMUNGAL et al [21] was noted, since the improvement gradually declined and no significant improvement was seen when comparing the PFTs on discharge with those gathered at the 4-week follow-up visit.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…48 Only two studies 49,50 were identified which compared in stable COPD patients the delivery of any short-acting bronchodilator using a pMDI, with or without spacer, to that of any other (at that time available) hand-held inhaler device, namely the DPIs Rotahaler ®49 or Turbuhaler ® . 50 No evidence of clinical difference in β-agonist delivery was found.…”
Section: Choice Of Inhaler Devices In Copdmentioning
confidence: 99%